Wood pellet as an alternative cooking fuel in Mozambique - Vesterberg, Jessica (2014)
The majority of the households in Mozambique rely on solid biomasses, such as charcoal and firewood, for their cooking practices. Combustion of solid biomass is a significant source of particulate and carbon monoxide (CO) emissions. Not only has the increasing demand of charcoal and firewood lead to an escalation of deforestation, but also the emissions from the combustion of the fuels are highly correlated to harmful health effects. Mozambique has vast natural recourses, especially forestland. The established wood processing industry in the country produces large amounts of by-products that could be compressed to the dense and high calorific fuel, wood pellets. This study compares the particulate and carbon monoxide emissions generated from wood pellets, birch firewood and torrefied bamboo pellets, when combusted in wood gasification stoves (WGS). Furthermore interviews were conducted with households and wood industry companies to investigate the possibility of introducing wood pellets in combination with WGS. The preferred fuel among the households was the torrefied bamboo pellet because of its smooth burning characteristic. Wood pellets had high flames, easily burning food. The laboratory tests showed that wood pellets had the lowest emissions of both CO and particulate matter (PM). Using torrefied bamboo pellets in the WGS would violate the WHO guidelines for human exposure of CO, 114 ppm for more than 15 minutes.